Quarter Life Crisis: Facing Reality That Doesn't Match Expectations and Plans - Putri Kurniawati, Amalia; Ningrum, Fiyona Yulita; Maulida, Marshanda Rachma; Putri, Najwa Raisya; Rahmadhani, Rizki Tri; Aulia, Syafa Nairah (Inovasi Lokal, 2023)
Quarter life crisis occurs when a person reaches the age of 18 to 29 years. A person will begin to find it difficult to face the world, find it difficult to control their emotions, and begin to question whether the life they are living is the right life. So there is a need for more information about the quarter life crisis. One solution that can be considered is to provide information and disseminate it so that individuals recognize and understand how to respond to the quarter life crisis by using posters. The research method used in this research is qualitative with a survey of Instagram posts with the characteristics of respondents, namely people aged 20 years and over who have Instagram and see posts that researchers have posted on the Instagram page. The instrument used was in the form of an Instagram post containing the meaning, characteristics and factors causing the quarter life crisis which were then analyzed using descriptive analysis. The results of this research show that the majority of respondents are experiencing a quarter life crisis. It is hoped that with this post about the quarter life crisis, they will be able to realize that they are experiencing a quarter life crisis and can face the appropriate measures.